The fiscal consequences of immigration: A study of local governments' expenditures - Matti E. E. Virén (Aboa Centre for Economics (ACE), 2022)
In this paper we examine how Finnish municipalities' expenditures depend on the share of citizens with foreign background out of the total population. Empirical analyses make use of Finnish panel data from 295 municipalities and 202 migrant nationalities for the period 1987- 2018. It turns out that the share of foreign population tends to increase per capita expenditures up to the point where the respective semi-elasticity is about one. The result seems robust in terms of different control variables, subsamples of the data and estimation techniques. Sizeable differences between different nationalities could, however, be detected. Thus, we cannot assume that the use of public services is neutral in terms of demographic changes and that should be considered when making assessments on overall fiscal effects of migration.
Keywords: H24; H31; H42; H71; J15; J61; 330; government expenditures; migration; local government